E-training environment for developing Capstone teaching skills for STEM teachers in Egypt - Noha Anbar; Tarek Hegazy; Mohamed El Naggar (European Scientific Journal, ESJ, 2024)
The research investigated the efficacy of utilizing an e-training environment to enhance capstone teaching skills among STEM educators. Conducted at Obour STEM School, Cairo, Egypt, the study employed a quasi-experimental design with 27 randomly selected participants. Three instruments were utilized: a list of Capstone teaching skills, a pre-post achievement test, and an observation card assessing skill acquisition in two main fields: EDP Field and Process Management Field. These fields encompassed eight main skills, subdivided into 64 subskills. The researchers conducted pre- and post-testing, initially administering a 70-question pre-test followed by a month-long online training via Microsoft Teams. The training content aimed to address identified needs based on pre-test results. After the training, participants completed a post-test, which was repeated after another month. Results indicated a statistically significant difference (p<=0.05) between pre-test and post-achievement test scores, favoring the latter, suggesting improvement in Capstone teaching skills. Similarly, there was a significant difference (p<=0.05) between pre-test and post-observation card scores, indicating enhanced skill development. Conclusively, the study demonstrated the effectiveness of e-training, particularly employing the SOLE technique, in enhancing capstone teaching skills among STEM educators. Consequently, the researchers recommended the integration of e-training environments in STEM teacher development programs in Egypt.